SOCIAL STRATIFICATION OF COASTAL COMMUNITIES IN KAMPUNG NELAYAN SEBERANG BELAWAN I OF NORTH SUMATERA PROVINCE - Aritonang, Irene Agustina; Nugroho, Firman; Kusai, Kusai (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRACT This research has been done in March 2018, located in Kampung Nelayan Seberang across Belawan I, North Sumatra Province. The study aims to: 1) Describe the structure of social stratification that occurs in communities in the Kampung Nelayan Seberang, and 2) Describe the structure of social differentiation found in the Kampung Nelayan Seberang. The method used in this study is a qualitative method with the determination of informants by purposive sampling. Based on the results of the research obtained, the social stratification that occurred in the Kampung Nelayan Seberang caused a difference in strata among the community, caused by factors charismatic, honor, education, and wealth. So as to cause class differences between the people, namely the upper class of society is occupied by people who have high income, respectable families, charismatic leaders. The middle class is a group of people who become fishermen owners, ambassadors, fuel suppliers, paramedics and private sector employees prioritizing economic aspects of power, and the influence of society in this group is limited to providing assistance in economic fulfillment. The people who belong to the lower class are those who have income > IDR. 1.000.000, namely fishermen, owners and labor fishermen. The differentiation that occurs in the neighboring Fisherman Village community has already existed and did not cause levels when viewed horizontally. Differences in professions, gender, migrants / non-migrants, tribes have been seen indirectly. This difference does not become a barrier to interaction between communities.Keywords: Stratification, Differentiation, Coastal Communities